2002
DOI: 10.1046/j.1524-4725.2002.02024.x
|View full text |Cite
|
Sign up to set email alerts
|

Mohs Micrographic Surgery for Melanoma: A Case Series, a Comparative Study of Immunostains, an Informative Case Report, and a Unique Mapping Technique

Abstract: MM, especially MIS on the head and neck, often exhibits an asymmetric growth pattern, making it quite suitable for treatment with MMS. The use of MART-1 immunostain may improve the diagnostic accuracy of Mohs surgeons. We believe that HMB-45 should not be used to rule out the diagnosis of MIS in equivocal sections because of its inferior sensitivity. We introduce a new mapping technique as an adjunctive measure to aid in the clinicopathologic evaluation of perilesional skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(127 citation statements)
references
References 91 publications
(175 reference statements)
2
122
3
Order By: Relevance
“…As suggested previously, 22 we also have had great difficulty obtaining properly oriented specimens when the tumor is excised by means of traditional , where diameter = (width + length)/2; radius = r. †t Test, P = .04. MMS bevel-cut margins, fixed in formalin, and then sent to the histopathology laboratory for paraffin embedding and en face sectioning.…”
Section: Mohsmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested previously, 22 we also have had great difficulty obtaining properly oriented specimens when the tumor is excised by means of traditional , where diameter = (width + length)/2; radius = r. †t Test, P = .04. MMS bevel-cut margins, fixed in formalin, and then sent to the histopathology laboratory for paraffin embedding and en face sectioning.…”
Section: Mohsmentioning
confidence: 99%
“…20 However, studies have demonstrated that more than 50% of LMs require margins greater than 5 mm, and that necessary margins are greater for larger lesions. 9,21,22 In addition, recurrence rates for standard excision of LM range from 8% to 20%. 16,18,23 More recently, the use of margin control surgical techniques has been advocated.…”
mentioning
confidence: 99%
“…34 Although margins of as little as 3 mm have also been recommended, 35 many subsequent studies using Mohs micrographic surgery have shown that narrow margins may not be adequate. [36][37][38][39][40][41] The optimal-margin controversy stems from the fact that no large-scale prospective controlled studies have examined margins for MIS. It is not surprising that the respondents in our study were divided between supporting a surgical margin of 5 mm or less (57.0%) and greater than 5 mm (33.3%) for MIS.…”
Section: Optimal Margin Controlmentioning
confidence: 99%
“…In this study, the histopathologic identification of melanoma in situ was aided by immunohistochemical staining of sections with MART-1, a marker for melanocytic differentiation. 7,8,[11][12][13][32][33][34] The increased sensitivity of MART-1 helped enhance the interpretation of specimens at the edge of the area defined by DELM. 8,35 In the hands of an experienced physician, dermoscopy has been shown to increase diagnostic accuracy com- pared with clinical visual inspection.…”
Section: -13mentioning
confidence: 99%